Isolation of halophilic bacteria - Abd Samad, Nadiah Syuhada; Amid, Azura (Springer Nature, 2018)
Protease the hydrolytic enzyme has very broad applications in industries. Identifying new protease source from food by isolating the protease producing microbe is consider a safe approach compare to isolating it from other sources which may be dangerous for human consumption. Therefore, this chapter discusses the method of isolating the microbial strain that can produce safe protease enzyme from fermented food.